(untitled) (Research, Society and Development, 2022)
Understanding the space of a watershed and the changes that take place in it over time is a strategy to favor the conservation of natural resources and elucidate practices conducive to the recovery of what has already been degraded. The case study aimed to understand the Pajeú river watershed in Pernambuco and the problems that hinder its preservation and recovery, namely that devastation practices that affect the Pajeú river prevail over it, leading to the decrease of its flow over the years. The methodology was based on aspects indicated and contextualized by authors of specific literature and, in association, the application of geoprocessing was integrated in order to address some issues dynamically and better understand the space and the transformations. Configuring itself with a quali-quanti nature, the methodology was based on authors who guide the acquisition and analysis of data for this purpose. It was concluded that the main problems are linked to the systematic deforestation over time, followed by fires with consequent soil erosion, originating from the unbalanced use of natural resources and have led to the devastation of the Caatinga biome in this region of the Brazilian semi-arid region. The main spring of the Pajeú River ceased to spill water in 1986, as did so many others along its 353 km, whose prospect of having flowing, perennial waters again is linked to changes in practices and in the use of natural resources in this, the largest hydrographic basin in the state of Pernambuco.